Penegakan Hukum Tindak Pidana Kekerasan Dalam Rumah Tangga Kepada Istri Berdasarkan Undang - Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga: (Studi Kasus di Polres Mojokerto) - Mochamad Ryo Anharum; Rachmat Ihya (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Household is the smallest part of a relationship that exists in society. Families formed within the bonds of marriage norms aim to form harmonious relationships. In fact, not all household is harmonious. The emergence of problem is often resolved in an unethical way, by using violence. Domestic Violence is efined as various forms of violence or threats of violence (physical, psychological, emotional, sexual, and neglect) to control their family members. To arrange the increase of Domestic Violence, the government make Act No. 23 of 2004 which specifically arrange the removal of Domestic Violence, as "a legal umbrella" that can give protection for the Domestic Violence vixtim’s. One example of law enforcement implementation according to Act No. 23 of 2004 that arrange the removal of Domestic Violence has been implemented by Polres Mojokerto in Case of Domestic Violence done by the defendant Boby Exzandro Wardhanny (BEW) Bin Suyatno to the victim, the defendant's wife, Iis Yuliatin (IY). The defendant had physically abused to the victim by grabbing and hitting the victim's right head that make pain in her right ear and bruises behind the right ear that stated in case register number : 75/Pid.Sus/2022/PN Mjk.